Environmental Approaches to Poultry Feed Formulation and Management - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2006)
Increasing environmental pressures on the poultry industry challenge the status quo of ecological stewardship. Faced with this critical oversight, nutritionists, poultry and soil scientists, and pollution specialists are creatively proposing bundled strategies dealing with various practices related to dietary manipulation, poultry litter management and feed additive utilization to palliate the potential environmental impact of poultry production. Their implementation has proved beneficial to both, the poultry industry and the environment.